INTEGRASI GAME EDUKASI DALAM PEMBELAJARAN BAHASA ARAB UNTUK GEN Z: STUDI LITERATUR - khoirunnisa nisa; M Pradipta Arief Niama Niama; Sufyani Fadlan Alaena Alaena (UIN Maulana Malik Ibrahim Malang, 2026)
The development of digital technology requires innovation in Arabic language teaching for Generation Z, who prefer visual-interactive and multimodal learning methods. This study examines the differences between conventional methods and the characteristics of Gen-Z, as well as the complexity of the Arabic language. This research uses a library research method with a qualitative descriptive approach, where the literature is analyzed using content analysis techniques that include reduction, presentation, and conclusion drawing. The results of the discussion show that the application of educational games such as Quizizz, Wordwall, and Educandy is effective in increasing motivation, active participation, and vocabulary mastery. However, challenges arise due to limitations in infrastructure and teachers' digital literacy. In conclusion, the integration of educational games is an integral educational need for Gen-Z in the digital age. This study suggests the Pedagogy-Embedded Game Centric Learning (PEGaCeL) framework and the Contextual Gamification Learning Cycle (SBGK) as comprehensive integrated solutions.